Greek religion and culture, the Bible, and the ancient Near East - Bremmer, Jan N. (Jerusalem Studies in Religion and Culture, 2008)
In the last decades there has been an increasing interest in the relationship between Greek religion andamp; culture and the Ancient Near East. This challenging book contributes greatly to this interest by studying the Near Eastern background of important Greek myths, such as those of the creation of the world and the first woman, the Flood, the Golden Fleece, the Titans and travelling seers, but also of the births of Attis and Asclepius as well as the origins of the terms 'paradise' and 'magic'. It also shows that, in turn, Greek literature influenced Jewish stories of divine epiphanies and that the Greek scapegoat myths and rituals contributed to the central Christian notion of atonement.